2021
DOI: 10.18632/oncotarget.27952
|View full text |Cite
|
Sign up to set email alerts
|

Inhibitory effects of Tomivosertib in acute myeloid leukemia

Abstract: The MAPK-interacting kinases 1 and 2 (MNK1/2) have generated increasing interest as therapeutic targets for acute myeloid leukemia (AML). We evaluated the therapeutic potential of the highly-selective MNK1/2 inhibitor Tomivosertib on AML cells. Tomivosertib was highly effective at blocking eIF4E phosphorylation on serine 209 in AML cells. Such inhibitory effects correlated with dose-dependent suppression of cellular viability and leukemic progenitor colony formation. Moreover, combination of Tomivosertib and V… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 77 publications
1
12
0
Order By: Relevance
“…Tomivosertib activity in models of various cancers is associated with potent inhibition of eIF4E phosphorylation at S209 [13,22,24]. In gastric cancer, our mechanism analysis indicates that (1) MNK/ eIF4E/β-catenin is responsible for tomivosertib activity, (2) MNK/eIF4E regulates β-catenin expression and activity, (3) tomivosertib decreases β-catenin level via eIF4E-mediated translation but not CK1-mediated degradation, and (4) p-eIF4E is dispensable for gastric cancer cell viability (Figures 3 and 4).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Tomivosertib activity in models of various cancers is associated with potent inhibition of eIF4E phosphorylation at S209 [13,22,24]. In gastric cancer, our mechanism analysis indicates that (1) MNK/ eIF4E/β-catenin is responsible for tomivosertib activity, (2) MNK/eIF4E regulates β-catenin expression and activity, (3) tomivosertib decreases β-catenin level via eIF4E-mediated translation but not CK1-mediated degradation, and (4) p-eIF4E is dispensable for gastric cancer cell viability (Figures 3 and 4).…”
Section: Discussionmentioning
confidence: 99%
“…As a MNK inhibitor, tomivosertib has been shown to act on cancer cells via suppressing eIF4E [13,22]. Given the importance of eIF4E signaling in gastric cancer [9,10], we investigated if eIF4E is the molecular target of tomivosertib.…”
Section: Tomivosertib Inhibits Eif4e and β-Catenin In Gastric Cancer ...mentioning
confidence: 99%
“… 79 Most recently, our group tested tomivosertib in the same established AML cell lines and also saw a reduction in cell viability and colony formation with the highest potency against MV411, MM6 cells, and KG-1 cells. 9 Through these four studies, we have found that MNK inhibitors ranging from unselective multi-kinase to very MNK specific all have antineoplastic effects in AML models.…”
Section: Mnk Inhibitors In Preclinical Leukemia Studiesmentioning
confidence: 98%
“… 77 Tomivosertib showed synergistic effects in viability and colony formation reduction with venetoclax, a BCL2 inhibitor approved in CLL and AML in combination with hypomethylating agents or low-dose chemotherapy. 9 Combination targets as well as dual MNK inhibitors are highlighted in Table 3 .…”
Section: Preclinical Combination Studies Using Mnk Inhibitorsmentioning
confidence: 99%
See 1 more Smart Citation